Ulaanbaatar Financial Self-Assessment - World Bank (Washington, DC, 2014)
The note is part of a broader technical assistance program designed to assist the City of Ulaanbaatar (UB) to improve its financial management system, assess the quality of municipal services provision, and mobilize resources from the capital markets to fund urban infrastructure. The note reviews factors that may support or constrain the rating, ultimately impacting the UB's creditworthiness. This assessment comprises of a comprehensive review of the city's economic fundamentals, institutional framework, fiscal performance, debt profile, and governance system. A key component of a credit rating comprises a review of the institutional framework that governs the city's financial system. This includes evaluating the legal framework, regulations, and procedures. The review also elucidates the jurisdictional parameters across levels of governments regarding debt raising and financing, and evaluates the overall quality of decision-making. As in a formal rating, the assessment also examines the operating environment, which is underlined by the sub-sovereign credit rating, and the support range, or the sovereign guarantee available to UB, if any. The exercise aims to reveal capacity gaps and potential areas for strengthening, as well as proposing concrete steps to improve the city's creditworthiness.